Advanced Electrochemical Biosensors (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
With the progress of nanoscience and biotechnology, advanced electrochemical biosensors have been widely investigated for various application fields. Such electrochemical sensors are well suited to miniaturization and integration for portable devices and parallel processing chips. Therefore, advanced electrochemical biosensors can open a new era in health care, drug discovery, and environmental monitoring. This Special Issue serves the need to promote exploratory research and development on emerging electrochemical biosensor technologies while aiming to reflect on the current state of research in this emerging field.